Decolonial subjectivities in participatory action research: Resident researcher experiences in the 2021 Guåhan Survey. Issue 1 (March 2023) - Lee, Kevin Lujan; Phan, Ngoc T; Flores, Nolan; Mesngon, Josiah Gabriel; Palaganas, Aria; Quichocho, Chauntae; San Agustin, Nikki Aubree
Scholarship on participatory action research (PAR) has come a long way since its foundations in Paulo Freire. However, it leaves much room to understand the personal transformations at stake in everyday residents' participation in PAR—a key mechanism through which PAR contributes to long-term social change in local communities. This literature gap is particularly salient for decolonial PAR, which incorporates Indigenous communities at every stage of the research process, and which is explicitly committed to the political goal of decolonization (i.e. the repatriation of Indigenous lands and oceans). Borrowing heavily from feminist geographical PAR scholarship, we articulate the concept of "decolonial subjectivities" to capture the dynamic, embodied ways in which resident researchers in decolonial PAR connect their own knowledge, experiences, and relationships with ongoing local struggles for Indigenous sovereignty. We then elaborate on this concept through a qualitative analysis of four waves of weekly reflections from five resident researchers in a decolonial PAR project in Guåhan—a modern-day colony, unincorporated territory of the United States, and the southernmost island of Låguas yan Gåni (or the Mariånas archipelago). We find two distinct shifts in resident researchers' decolonial subjectivities over time: (1) deepening embodied connection to decolonization through situating one's role in decolonization within a broader set of familial and community relationships; and (2) deepening embodiment of role as decolonial researchers through affirming one's expertise and power to effectuate change as a researcher supporting and facilitating the continued, ongoing struggle for Indigenous sovereignty.